2019
DOI: 10.1096/fj.201902043r
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric functions of a binuclear metal center within the transport pathway of a human zinc transporter ZIP4

Abstract: Abbreviations: BbZIP, ZIP from Bordetella bronchiseptica; BMC, binuclear metal center; DDM, n-Dodecyl-β-D-Maltopyranoside; DPBS, Dulbecco's phosphate-buffered saline; FBS, fetal bovine serum; hZIP4, human ZIP4; LCP, lipidic cubic phase; SERCA, sarco/endoplasmic reticulum Ca2+-ATPase; ZIP, Zrt-/Irt-like protein. AbstractMetal clusters are exploited by numerous metalloenzymes for catalysis, but it is not common to utilize a metal cluster for substrate transport across membrane.The recent crystal structure of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 33 publications
3
79
0
Order By: Relevance
“…As shown in Figure 2A, in sharp contrast to the wild type hZIP4, none of the cells expressing any variants uptook more zinc than the blank group in which the cells were transfected with an empty vector, which means that the variants have no detectable zinc transport activity with 10 µM of Zn 2+ added in culture media. For the wild type hZIP4, the previous studies have shown that zinc transport activity reaches plateau at 10 µM of Zn 2+ under the same condition (28,29). To examine whether any activity can be detected at higher zinc concentration, the P200L variant was tested at various zinc concentrations up to 50 µM, but the results only confirmed no detectable activity ( Figure S1).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…As shown in Figure 2A, in sharp contrast to the wild type hZIP4, none of the cells expressing any variants uptook more zinc than the blank group in which the cells were transfected with an empty vector, which means that the variants have no detectable zinc transport activity with 10 µM of Zn 2+ added in culture media. For the wild type hZIP4, the previous studies have shown that zinc transport activity reaches plateau at 10 µM of Zn 2+ under the same condition (28,29). To examine whether any activity can be detected at higher zinc concentration, the P200L variant was tested at various zinc concentrations up to 50 µM, but the results only confirmed no detectable activity ( Figure S1).…”
Section: Resultsmentioning
confidence: 83%
“…In this work, we characterized all the seven AE-causing mutations, including four homozygous mutations (C62R, P200L, Q303H and C309Y) (5,6,25,26) and three heterozygous mutations (R95C, A99T and N106K) (6,26,27), and studied their impacts on hZIP4 function. The hZIP4 variants with a Cterminal HA tag were transiently expressed in HEK293T cells and applied to the cell-based radioactive zinc transport assay (6,7,28,29). As shown in Figure 2A, in sharp contrast to the wild type hZIP4, none of the cells expressing any variants uptook more zinc than the blank group in which the cells were transfected with an empty vector, which means that the variants have no detectable zinc transport activity with 10 µM of Zn 2+ added in culture media.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second mode, through certain significant dynamics, the BMC is transiently exposed to both sides so that it is located in the middle of a pore with two ends opening simultaneously, a characteristic of channels. Cell-based metal transport assays using either radioactive substrate or metal-responsive fluorescence dye on the ZIPs from E.coli to multiple eukaryotes have shown Michaelis-Menten kinetics [1,3,23,31,32,[36][37][38][39][40][41], supporting the carrier mode. However, the study of BbZIP reconstituted in proteoliposomes indicated that the transport is non-saturable, which supports the channel mode [42].…”
Section: Inward-facing Conformation and Implications On Transport Mecmentioning
confidence: 97%
“…A BMC is often observed at the active site of metalloenzymes or the soluble portion of metal transporters [29,30], but rare in the middle of the transport pathway. A survey of over 17,000 ZIPs indicated that a BMC is present in many ZIPs from a variety of species, suggestive of an important role in ZIP function [31]. Mutagenesis and transport assay of HsZIP4 showed that the M1 is absolutely required for transport, whereas eliminating the M2 or occupying the M2 by a lysine residue only reduced but did not completely abolish transport activity.…”
Section: A Binuclear Metal Center (Bmc) In the Middle Of The Transpormentioning
confidence: 99%